Webinar Inovasi dan Adaptasi pada mahasiswa FEB Universitas Klabat dalam rangka meningkatkan minat berwirausaha - Lelengboto, Abraham; Wardoyo, Sharon Kumaratih Dewi (Universitas Klabat, 2024)
The government believes that entrepreneurship is one of the economic drivers for Indonesia to be able to compete globally. Kemendikbudristek is doing this by promoting the “Wirausaha Merdeka” program in the hope that students will gain real experience and understanding of entrepreneurship. The Faculty of Economics and Business of Klabat University, through the Student Association (HIMA) in the academic advancement department, raised the title “The importance of innovation and adaptation in business” as an attempt to raise the interest of entrepreneurial students. This webinar highlights the theory of creative destruction and disruptive innovation and aims to improve students' understanding of entrepreneurship, innovation, and adaptation. The presenter leads the seminar through lectures and open discussion. The goal of this webinar is to increase the understanding of the subjects delivered. Zoom is the media for this webinar, and the total number of participants in this event is ninety-two students. Pre- and post-tests are the tools used to measure the success of the webinar. The results of the test showed that there was an improvement in students' understanding of innovation, creative destruction, and disruptive innovation. Through this webinar, students gain an understanding of the theme of entrepreneurship that will affect their perception and attitude toward being entrepreneurs.